A study on the diagnostic value of artificial intelligence combined with a contrast-enhanced ultrasound scoring system in partially cystic thyroid carcinoma - Yan, Xiao-Hui; Chen, Qian; Xin, Yu-Wei; Yuan, Si-Jie; Liu, Jing-Jing; Jia, Hai-Yan; Wen-Ya,; Zhang, Yan-Jing; Fan, Wen-Wen; Zhao, Yu-Fang; Liang-Ping,; Liu, Li-Ping (Frontiers in Endocrinology, 2025)
ObjectivesThe aim of this study was to investigate the diagnostic value of the contrast-enhanced ultrasound (CEUS) scoring system, artificial intelligence (AI) and the American College of Radiology Thyroid Imaging and Reporting Data System when used by sonographers of different seniority levels individually and in combination for the diagnosis of partial cystic thyroid nodules (PCTNs).Materials and methodsA retrospective analysis of conventional ultrasound and CEUS images of enrolled patients was performed, and a CEUS scoring system was established. The sensitivity, specificity, and area under the curve (AUC) of CEUS and AI individually and in combination for diagnosis were compared among sonographers with different seniority levels.ResultsA total of 166 nodules (83 benign and 83 malignant) from 152 patients with PCTNs were analyzed in this study. Nine CEUS features of PCTNs were observed and summarized; eight of these features differed between the two groups (all p < 0.05) and were included in the CEUS scoring system. CEUS and AI used by junior and senior physicians effectively diagnosed PCTNs. AI improved the diagnostic efficacy of junior physicians. AI assistance combined with CEUS had the best diagnostic efficacy, with an AUC=0.985 for senior physicians and an AUC=0.967 for junior physicians, with no significant difference (P>0.05).ConclusionsThe CEUS scoring system established in this study has high diagnostic value for PCTNs. The use of CEUS and AI can improve the diagnostic accuracy of sonographers and improve the prognosis of PCTN patients.